Phobias a handbook of theory, reserach and treatment - Davey, Graham C.L (John Wiley & Sons, 1997)
This book describes the symptoms, prevalence rates, individual case histories and etiology of phobias. It explores treatment and covers current methodologies, outcome efficacy, and comparisons between different therapeutic techniques.